2014
DOI: 10.3389/fpsyg.2014.00915
|View full text |Cite
|
Sign up to set email alerts
|

What have we learned about the processes involved in the Iowa Gambling Task from developmental studies?

Abstract: Developmental studies using the Iowa Gambling Task (IGT) or child-friendly adaptations of the IGT converged in showing that children and adolescents exhibit a strong bias in favor of disadvantageous choices whereas adults learn to decide advantageously during the course of the task. In the present article, we reviewed developmental studies that used the IGT or child-friendly adaptations of the IGT to show how these findings provide a better understanding of the processes involved in decision-making under uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 39 publications
(85 reference statements)
6
43
1
Order By: Relevance
“…In other words, control subjects seemed able to consider both the frequency of losses and the long-term outcome during the IGT-i.e., they favored the good decks and the decks with low frequency of losses. In that sense, our results corroborated those of developmental studies which demonstrated that only healthy adults seemed to consider both loss frequency and final outcome in an adapted version of the IGT (Aïte et al, 2012;Cassotti, Aïte, Osmont, Houdé, & Borst, 2014).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In other words, control subjects seemed able to consider both the frequency of losses and the long-term outcome during the IGT-i.e., they favored the good decks and the decks with low frequency of losses. In that sense, our results corroborated those of developmental studies which demonstrated that only healthy adults seemed to consider both loss frequency and final outcome in an adapted version of the IGT (Aïte et al, 2012;Cassotti, Aïte, Osmont, Houdé, & Borst, 2014).…”
Section: Discussionsupporting
confidence: 94%
“…In conclusion, our study confirms the findings of publications that address the influence of gain-loss frequency in analyzing control subjects' performance on the IGT, and showed that healthy adults are not only guided by the long-term outcome but also by the frequency of loss (Aïte et al, 2012;Beitz et al, 2014;Cassotti et al, 2014). These developmental studies also indicate that impaired performances on the IGT of both children and older adults are due to a loss frequency bias-i.e.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Finally, though the present data do not directly indicate the mechanisms for the age differences uncovered in this research, we don't rule out that the possibility that the difference observed between younger and older adolescents may depend also on the neuroanatomical and neurofunctional development of the prefrontal cortex across childhood and adolescence, given that several studies have demonstrated that younger adolescents are more "myopic for the future" than late adolescents and adults in decision-making behavioral tasks, such as the Iowa Gambling Task (Cassotti, Houdé, & Moutier, 2011;Cauffman et al, 2010;Crone & Dahl, 2012;Crone & van der Molen, 2004;Hooper, Luciana, Conklin, & Yarger, 2004;; see Beitz, Salthouse, &Davis, 2014 andCassotti, Aïte, Osmont, Houdé, &Borst, 2014 for reviews).…”
Section: Discussionmentioning
confidence: 89%